(untitled) (Al-Quds Journal for Natural Sciences, 2022)
Munir A. Al-Zeer Department of Applied Biochemistry, Technical University of Berlin, Berlin-Germany Abstract For several decades, biomedical research has traditionally relied on the use of two-dimensional (2D) cell culture and animal models to study human biology and diseases. However, it can be difficult to address questions that are relevant to human biology and diseases in animal models or 2D cell culture, such as genetics, development, immune response, and cell host tropism. Furthermore, scarcity of advanced in vitro and in vivo models has hindered progress in understanding disease causes and, as a result, the creation of innovative therapeutic methods for patients. To improve our understanding and the current situation, more physiologically and realistic research models for mechanism-based target identification, drug development and screening, developmental biology, cancer and infectious diseases are needed.